Religious Blasphemy in Indonesia - Yunus, Ahyuni; Hatta, Muhammad; Rapik, Mohamad; Badaru, Baharuddin (International Journal of Psychosocial Rehabilitation, 2020)
Religion in Indonesia is very pluralistic or majmuk. Every person is obliged to embrace a religion or belief that is believed to be true. Religion and beliefs have become the basic rights of every Indonesian citizen. The basis of religious freedom in Indonesia is regulated in Article 28E, Article 28I, Article 29 of the 1945 Constitution and Article 4, Article 22 of Law No. 39 of 1999 concerning Human Rights. However, this freedom is not mutlat and must be limited to protect religious harmony in Indonesia. One of the actions that often triggers religious disputes is the crime of blasphemy or blasphemy of religion both directly and through various online media. To maintain religious harmony, the government issues Law No. 1 of 1946 concerning the Criminal Code, Law No. 1 / PNPS / 1965 concerning Prevention of Abuse and / or Blasphemy of Religion, Law No. 40 of 2008 concerning the Elimination of Racial and Ethnic Discrimination, Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Electronic Transaction Information. In addition to legal action against the perpetrators of religious blasphemy, the government and the community must work together to maintain religious tolerance and prevent fanaticism towards each other’s religious identity so that it has the potential to create horizontal conflicts between religious adherents in Indonesia.